2010
DOI: 10.1016/j.jcin.2010.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Pulmonary Valve Implantation in the Young

Abstract: Percutaneous pulmonary valve implantation is feasible and safe in the young with dysfunctional RVOT conduits. An improvement in symptoms, hemodynamic status, and objective findings of exercise performance occurs. Early follow-up demonstrates persistent improvement in ventricular parameters, PR, and objective exercise capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 34 publications
7
62
2
2
Order By: Relevance
“…PPVI leading to restoration of pulmonary valve function, similarly to PVR, simultaneously being a less invasive method, could be expected to have a positive effect on heart function and consequently exercise performance. There is, however, no clear evidence of improvement in cardiopulmonary function after the procedure [11,15,18,20,21]. In our study, a small but significant improvement in peak VO 2 and EQCO 2 were reported.…”
Section: Discussioncontrasting
confidence: 68%
“…PPVI leading to restoration of pulmonary valve function, similarly to PVR, simultaneously being a less invasive method, could be expected to have a positive effect on heart function and consequently exercise performance. There is, however, no clear evidence of improvement in cardiopulmonary function after the procedure [11,15,18,20,21]. In our study, a small but significant improvement in peak VO 2 and EQCO 2 were reported.…”
Section: Discussioncontrasting
confidence: 68%
“…Two-dimensional transthoracic echocardiography was performed on a Phillips IE-33 (Andover, Massachusetts) machine using accepted methods, 2,10 with a standardized clinical protocol performed by a research sonographer. Data were retrieved from clinical reports with missing or outlying data points reviewed by 1 of the authors (S. Borik).…”
Section: Echocardiographymentioning
confidence: 99%
“…Data were retrieved from clinical reports with missing or outlying data points reviewed by 1 of the authors (S. Borik). RV enddiastolic (RVED) dimension and left ventricular (LV) ejection fraction were measured using m-mode in the parasternal short axis cut of the ventricles 2 and RV systolic pressure (RVSp) estimated using continuous wave Doppler from the tricuspid regurgitation jet velocity plus 5 mm Hg. Z-scores were calculated using accepted pediatric values.…”
Section: Echocardiographymentioning
confidence: 99%
See 1 more Smart Citation
“…Négy centrumban 36 betegen el végzett percutan beavatkozás után egy évvel a reinter venciómentes-ség 97% volt, egy billentyűt kellett sebé szileg kicserélni [19]. Vezmar és mtsai [20] 28 betegen elvégzett hasonló beavatkozását követően az RVEDV jelentősen csökkent, 36 hónap után a műtétmentesség 83%, az intervenció-mentesség 80% volt.…”
Section: áBraunclassified